2008
DOI: 10.1177/0269881107082901
|View full text |Cite
|
Sign up to set email alerts
|

Change in sexual dysfunction with aripiprazole: a switching or add-on study

Abstract: Sexual dysfunction and raised prolactin are common adverse effects of many anti-psychotics. Aripiprazole is an atypical anti-psychotic associated with a reduction in prolactin level in anti-psychotic-induced hyperprolactinemia. Our hypothesis was that switching from another anti-psychotic to aripiprazole would be associated with a reduction in sexual dysfunction. An open label switch to aripiprazole was offered to 27 subjects with inadequate therapeutic response or intolerance to another anti-psychotic, who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 18 publications
0
45
0
2
Order By: Relevance
“…Hyperprolactinemia is rapidly reversed following the discontinuation of amisulpride treatment (20) or once the patient has been switched to a prolactin-sparing antipsychotic, such as quetiapine (21), olanzapine, ziprasidone or aripiprazole. The addition of the partial agonist aripiprazole (22), including the use of dopamine agonists, to the treatment was an alternative approach. However, thi is associated with a risk of worsening or inducing psychosis, which would require specialist services.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperprolactinemia is rapidly reversed following the discontinuation of amisulpride treatment (20) or once the patient has been switched to a prolactin-sparing antipsychotic, such as quetiapine (21), olanzapine, ziprasidone or aripiprazole. The addition of the partial agonist aripiprazole (22), including the use of dopamine agonists, to the treatment was an alternative approach. However, thi is associated with a risk of worsening or inducing psychosis, which would require specialist services.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [13][14][15][16] have shown that switching from prolactin-raising antipsychotics to aripiprazole is useful for treating antipsychotic-induced hyperprolactinemia in schizophrenic patients, with no significant changes in overall psychopathology. However, clinicians generally hesitate to change antipsychotic regimens, especially in clinically stable patients maintaining a high level of functioning, since such a strategy is sometimes accompanied by the risk that psychotic symptoms may worsen later.…”
Section: Discussionmentioning
confidence: 99%
“…In males, after switching treatment to aripiprazole, ejaculatory difficulty was significantly reduced [Mir et al 2008]. A descending view in one study did not find such correlation between elevated prolactin level and antipsychotic-induced sexual dysfunction [Westheide et al 2008].…”
Section: In Patients On Drug Treatment For Other Conditionsmentioning
confidence: 97%
“…Increase in serum prolactin level in patients with schizophrenia during antipsychotic treatment correlated with orgasmic dysfunction [Rettenbacher et al 2010]. In patients treated with prolactin-raising and prolactinsparing antipsychotics, EjD was associated with the prolactin raising medications [Knegtering et al 2008].Aripiprazole is an antipsychotic associated with a reduction in prolactin level in antipsychoticinduced hyperprolactinemia [Mir et al 2008]. In males, after switching treatment to aripiprazole, ejaculatory difficulty was significantly reduced [Mir et al 2008].…”
mentioning
confidence: 99%